2018
DOI: 10.1038/s41533-018-0098-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced bronchoconstriction: prevalence, pathophysiology, patient impact, diagnosis and management

Abstract: Exercise-induced bronchoconstriction (EIB) can occur in individuals with and without asthma, and is prevalent among athletes of all levels. In patients with asthma, symptoms of EIB significantly increase the proportion reporting feelings of fearfulness, frustration, isolation, depression and embarrassment compared with those without symptoms. EIB can also prevent patients with asthma from participating in exercise and negatively impact their quality of life. Diagnosis of EIB is based on symptoms and spirometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 73 publications
(154 reference statements)
0
91
0
9
Order By: Relevance
“…On the one hand, in most children with asthma, exercise could be considered a trigger of asthma symptoms, inducing bronchospasm; it can also be a unique asthma phenotype (Chupp et al, 2017). On the other hand, it is well noted that low physical fitness in childhood is linked to the development of asthma in young adulthood (Koczulla et al, 2017;Aggarwal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, in most children with asthma, exercise could be considered a trigger of asthma symptoms, inducing bronchospasm; it can also be a unique asthma phenotype (Chupp et al, 2017). On the other hand, it is well noted that low physical fitness in childhood is linked to the development of asthma in young adulthood (Koczulla et al, 2017;Aggarwal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.1101/2020.01.10.20016956 doi: medRxiv preprint Patients referred to pediatric pulmonary division for exertional dyspnoea or chest tightness without a clear history of asthma and/or where the history suggested that symptoms were not controlled with an inhaled beta-2 agonist. N=32, mean age (age range): 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Clinical history and treadmill exercise-challenge test and pulse oximeter to measure end-tidal O2 and CO2. Running at 85% of aerobic capacity for 6 minutes.…”
Section: Statement Of Ethicsmentioning
confidence: 99%
“…Regarding the osmotic theory, which is currently the most accepted, the hyperventilation through the mouth associated with intense exercise requires the humidification and heating of large volumes of air in a short period of time, leading to airway dryness. Water loss by evaporation in airway surfaces is associated with events that can trigger the contraction of bronchial smooth muscle, such as mast cell degranulation [5], which releases pro-inflammatory mediators that are involved in smooth muscle contractions, mucus production, and microvascular permeability, leading to airway edema and bronchoconstriction [5,6]. Furthermore, as mentioned in the review from Couto et al [7], epithelial damage can also be involved in EIB, and several studies have demonstrated increased infiltration of eosinophils, neutrophils, and/or epithelial cells associated with EIB, as well as an increase in airway inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of EIB diagnosis, it is important to clarify that the clinical history and the presence of typical symptoms (dyspnea, chest tightness, cough, and wheeze) can be used only as a complement to determine the occurrence of EIB [9], since valid diagnoses of EIB should be established though direct or indirect tests. For instance, the methacholine challenge is direct, whereas the eucapnic voluntary challenge as well as the standardized treadmill exercise test-whereby exercise may be followed by a decrease of 10 % or more in forced expiratory volume (FEV1) compared to pre-exercise levels-are indirect tests [6,7,9]. It is worthy to mention that, for some authors [10,11], the standard treadmill exercise test is preferred for EIB due to its resemblance to real-life exercise.…”
Section: Introductionmentioning
confidence: 99%